2021
DOI: 10.4236/tel.2021.111003
|View full text |Cite
|
Sign up to set email alerts
|

Cash Holdings in Shariah-Compliant Firms

Abstract: The restrictions of a shariah-compliant index could have consequences for corporate finance. This research investigates the difference in cash holding policies between shariah-compliant and conventional firms in the Indonesia capital market. Our empirical results suggest that a shariah-compliant firm holds significantly less cash compared to a conventional firm. The empirical finding still maintains after excluding top performers in the market and after controlling for other proxies of cash holdings and sharia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…However, these studies did not investigate how cash holdings can variously impact the performance of Shariah-compliant and conventional firms. Subsequently, using a sample including Shariah-compliant and conventional firms from Indonesia over the years 2016, Hakim et al (2021 confirmed that the determinants of corporate cash holdings varied across the two sets of firms.…”
Section: Literature Review and Hypothesesmentioning
confidence: 84%
See 2 more Smart Citations
“…However, these studies did not investigate how cash holdings can variously impact the performance of Shariah-compliant and conventional firms. Subsequently, using a sample including Shariah-compliant and conventional firms from Indonesia over the years 2016, Hakim et al (2021 confirmed that the determinants of corporate cash holdings varied across the two sets of firms.…”
Section: Literature Review and Hypothesesmentioning
confidence: 84%
“…Islamic corporate finance literature confirmed that cash holdings decisions vary across Shariah-compliant and conventional firms (Alnori et al , 2021; Bugshan et al , 2021a; Hakim et al , 2021). More specifically, Bugshan et al (2021a) found that the cash holdings level is significantly higher in Shariah-compliant firms than their conventional counterparts operating in GCC markets.…”
Section: Literature Review and Hypothesesmentioning
confidence: 90%
See 1 more Smart Citation